Hypoxia-Inducible Angiopoietin-2 Expression Is Mimicked by Iodonium Compounds and Occurs in the Rat Brain and Skin in Response to Systemic Hypoxia and Tissue Ischemia - Mandriota, Stefano J.; Pyke, Charles; Di Sanza, Corinne; Quinodoz, Pierre; Pittet, Brigitte; Pepper, Michael S. (The American journal of pathology, 2000)
Angiopoietins are ligands for the endothelial cell tyrosine kinase receptor Tie-2. Ang-1, the major physiological activator of Tie-2, promotes blood vessel maturation and stability. Ang-2 counteracts this effect by competitively inhibiting the binding of Ang-1 to Tie-2. Using a combined RNase protection/semiquantitative reverse transcriptase-polymerase chain reaction approach, we demonstrate that hypoxia up-regulates Ang-2 mRNA levels by up to 3.3-fold in two human endothelial cell lines. In bovine microvascular endothelial (BME) cells, the flavoprotein oxidoreductase inhibitor diphenylene iodonium (DPI) and the related compound iodonium diphenyl mimic induction of Ang-2 but not vascular endothelial growth factor (VEGF) by hypoxia; in combination with hypoxia, DPI further increases Ang-2 expression but has no effect on the induction of VEGF by hypoxia. Neither Ang-2 or VEGF was increased by cyanide or rotenone, suggesting that failure in mitochondrial electron transport is not involved in the oxygen-sensing system that controls their expression. In ischemic rat dorsal skin flaps or in the brain of rats maintained for 12 hours under conditions of hypoxia, Ang-2 mRNA was up-regulated 7.5- or 17.6- fold, respectively. VEGF was concomitantly increased, whereas expression of Ang-1, Tie-2, and the related receptor Tie-1 was unaltered. In situ hybridization localized Ang-2 mRNA to endothelial cells in hypoxic skin. These findings 1) show that up-regulation of Ang-2 by hypoxia occurs widely in endothelial cells in vitro and in vivo; 2) suggest that induction of Ang-2, but not VEGF, by hypoxia in BME cells is controlled by a flavoprotein oxidoreductase that is sensitive to iodonium compounds; and 3) point to Ang-2 and VEGF as independently regulated and selective effectors of hypoxia-induced vascular sprouting.